Law Enforcement for the Crime of Insulting the Government in Relation to the Principle of Ultimum Remedium in the Perspective of the Right to Freedom of Expression - Shelma Shetty Pinem; Lies Sulistiani; Budi Arta Atmaja (Universitas Islam Sultan Agung, 2026)
This study examines law enforcement practices or state responses to the crime of insulting the government and how this principle of ultimum remedium works in law enforcement of the crime of insulting the government in Indonesia. Through comparative study methods with countries outside Indonesia, literature studies, and interviews with law enforcement officials to see their law enforcement practices from the perspective of law enforcement. The results of the study show that although the 2023 Criminal Code has regulated insults against the government as an absolute complaint, the norm still leaves room for multiple interpretations between criticism and insults. Law enforcement practices in Indonesia show a tendency to use criminal law as the primary instrument (primum remedium), although normatively recognizing ultimum remedium so that clearer limits, strengthening non-criminal mechanisms, and procedural safeguards are needed to be in line with freedom of expression in a democratic country. This study aims to find out the practice of law enforcement and how this principle of ultimum remedium is present in law enforcement.